Rancang Bangun Sistem Informasi Antrian dan Pendaftaran Rawat Jalan Rumah Sakit Medika Lestari - Mohammad Irham Akbar; Hyanang Trie Novka (Jurnal Universal Technic, 2023)
Queue printers and outpatient registration are systems used in hospitals to help speed up the patient registration process and provide a better patient experience. This system uses information technology to automate the registration process, reduce waiting times and prevent crowding in the registration area. After receiving the queue number, the patient then waits for a call to get an examination or service. The system can be programmed to provide information about expected waiting times, enabling patients to make more effective use of their time. The outpatient registration system uses information technology to help patients speed up the registration process, reduce waiting times, and optimize the use of resources, such as doctors' space and time. This system can also help improve the patient experience by providing convenience and comfort in the registration process. Overall, the use of queuing presses and outpatient registration systems can help improve efficiency and patient experience in a hospital, as well as optimize resource use.